ANALISA SISTEM ELEKTRONIK POWER STEERING UNTUK PENGEMBANGAN KENDARAAN LISTRIK FAKULTAS TEKNIK UNRAM - Okariawan, I Dewa Ketut; Made Wirawan; Bawa Susana, I G.; Maharsa Pradityatama (Energy, Materials and Product Design, 2024)
Recenly conventional vehicles use fossil fuels, however these fuels are non-renewable energy sources and their availability in nature is very limited. If they are explored continuously then one day they will run out, so it is very necessary to save and innovate to use these sources. Other renewable energy sources, one of which is electrical energy, where this electrical energy can be generated from various sources such as water, solar, biomass and so on. Besides that, the use of electrical energy for vehicles is currently very relevant because it is environmentally friendly, that is, it does not produce CO or CO2 gas like conventional vehicles, so this energy is known as green energy. Indonesia has the potential to produce electric cars because the availability of nickel is very abundant to be processed into batteries, as a provider or energy storage for electric cars, our country has a very big opportunity to produce electric cars. To make this happen, it is deemed necessary to carry out comprehensive studies such as power steering so that comfort and safety can be achieved. The most suitable power steering is the electric power steering (EPS) type because the energy required comes from the battery. The method applied in this research is an experimental method, by measuring torque requirements on various roads, the roads chosen are asphalt roads, block paving roads and dirt roads. Based on this data, an EPS test bench then created which was able to measure the input and output torque of the EPS and look for the power consumed by the system. Road conditions can cause differences in torque requirements, in block paving road conditions the greatest torque requirement is 2.77 Nm and the smallest occurs in asphalt road conditions at 1.62 Nm. EPS testing shows that it is only loaded up to 25% with an input torque of 1,652 Nm resulting an output torque of 3,924 Nm with an electrical power consumption of 6,31 watts.